EFFECT OF PRICE CHANGE OF LIVE CHICKENS AND FEED ON THE OPTIMAL LENGTH OF BROILER CHICKEN GROWING IN LOW-SCALE PRODUCTION - Grużewska, Agata (Acta Scientiarum Polonorum. Oeconomia, 2006)
The results of fourteen production cycles of broiler chickens, grown on a private farm situated close to Siedlce in the years 2003–2005, were analyzed in the research. The broiler growing was carried out in the intensive system including straw bedding and controlled feed utilization. Randomly selected chickens were weighed every seven days throughout the whole growing period. On the basis of the results obtained, parameters of a chicken growth polynomial curve were estimated. Moreover, production function parameters were estimated taking into consideration live chicken and feed prices. In addition, a feed cost function as well as an average and marginal product function were calculated. Production was divided into stages, taking into account the assumptions of the production function theory, and optimal length of the growing period for broiler chickens was determined according to the assumed changes in live chicken and feed prices.